ANALISIS KESALAHAN SISWA DI MTs ALKHAIRAT SIBALAYA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI PELUANG BERDASARKAN PROSEDUR NEWMAN DITINJAU DARI JENIS KELAMIN: Analysis of Errors Made by Students At MTs Alkhairat Sibalaya In Solving Story Problems on Probability Material Based on The Newman Procedure Viewed From Gender - Rifai, Mohammad; Idris, Mustamin; Rochaminah, Sutji; Karniman, Tegoeh S. (Universitas Tadulako, 2024)
This research aims to obtain a description of the mistakes of class IX students at MTs Alkhairat Sibalaya in solving word problems on chance material based on the Newman procedure in terms of gender. The subjects of this research were one male and one female student in class IXB MTs Alkhairat Sibalaya who made the most mistakes. This type of research is qualitative research with a descriptive approach. Data was collected by means of written tests and interviews. The data analysis techniques in this research are data condensation, data presentation, and drawing conclusions. The results of the study showed that female and male students had the same types of errors: Male students made (1) Process skills error types, namely making mistakes in carrying out calculations and not continuing the solution procedure (2) Types of errors in writing the final answer, namely not writing conclusion. Female students made (1) a type of process skill error, namely carrying out the wrong steps or procedure for solving a problem and (2) a type of error in writing the final answer, namely not writing a conclusion.